2021
DOI: 10.1002/ajhb.23711
|View full text |Cite
|
Sign up to set email alerts
|

Tibial cortical and trabecular variables together can pinpoint the timing of impact loading relative to menarche in premenopausal females

Abstract: Objectives: Though relationships between limb bone structure and mechanical loading have provided fantastic opportunities for understanding the lives of prehistoric adults, the lives of children remain poorly understood. Our aim was to determine whether or not adult tibial skeletal variables retain information about childhood/adolescent loading, through assessing relationships between cortical and trabecular bone variables and the timing of impact loading relative to menarche in premenopausal adult females. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 157 publications
0
1
0
Order By: Relevance
“…Within the current knowledge on metabolic differences and trade-offs between cortical and trabecular tissues through life, including during ontogeny, these discrepancies between the clear adaptations at the proximal tibia observed in Sansuke's corticotrabecular complex adjustment (Mazurier et al, 2010) and the less distinct structural changes at the underlying trabecular network are unexpected. Under experimental analyses the human tibial shaft (Erlandson et al, 2012;Weatherholt et al, 2013;Murray and Erlandson, 2022; for other skeletal elements see also Kontulainen et al, 2003;Eser et al, 2009;Erlandson et al, 2012) and mouse tibial shaft (De Souza et al, 2005;Brodt and Silva, 2010) show that cortical bone primarily reflects early life behaviour, while epiphyseal trabecular bone microarchitecture may primarily reflect adult loading. This is consistent with a recent study by Saers et al (2022) show- ing an adult-like trabecular structure in the calcaneum of 1.5-to 2-year-old Japanese macaques that recently adopted an adult-like locomotion (Saers et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Within the current knowledge on metabolic differences and trade-offs between cortical and trabecular tissues through life, including during ontogeny, these discrepancies between the clear adaptations at the proximal tibia observed in Sansuke's corticotrabecular complex adjustment (Mazurier et al, 2010) and the less distinct structural changes at the underlying trabecular network are unexpected. Under experimental analyses the human tibial shaft (Erlandson et al, 2012;Weatherholt et al, 2013;Murray and Erlandson, 2022; for other skeletal elements see also Kontulainen et al, 2003;Eser et al, 2009;Erlandson et al, 2012) and mouse tibial shaft (De Souza et al, 2005;Brodt and Silva, 2010) show that cortical bone primarily reflects early life behaviour, while epiphyseal trabecular bone microarchitecture may primarily reflect adult loading. This is consistent with a recent study by Saers et al (2022) show- ing an adult-like trabecular structure in the calcaneum of 1.5-to 2-year-old Japanese macaques that recently adopted an adult-like locomotion (Saers et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed differential gene expression and unique transcriptional profiles in cortical and trabecular bone tissues from mechanically loaded murine tibiae models [20,23,24], indicating that bone modeling may be mediated differently in these two bone tissues. Additional studies have demonstrated that bone modeling is usually more extensive and happens faster in trabecular bone compared to cortical bone (except for, possibly, endocortical surfaces), possibly due to the larger surface-to-volume ratio of trabecular bone tissue [18,19,21,22]. Together, these data suggest that trabecular bone in the extremities of long bones may hold a more discerning functional signal compared to cortical bone.…”
Section: Influencing Factors In Bone Modeling In Response To Mechanic...mentioning
confidence: 93%
“…The overall findings of these studies show that bone modeling in adults and mature animals still takes place, albite at a reduced rate [2,[25][26][27][28][29][56][57][58]. Nevertheless, while this decrease in responsiveness to mechanical stimuli with age has direct implications for the ability to infer changes in loading magnitude and direction of adults and mature animals, it is relevant when studying the locomotion behavior of an extinct species or in the deduction of physical activity differences between two distinct human populations, as the onset of these loads start at a young age and the loading signal was shown to be retained in adults [22].…”
Section: Influencing Factors In Bone Modeling In Response To Mechanic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Followed for eight years, the jumpers maintained elevated bone mineral content (BMC) at the hip (Gunter et al 2008). More recent studies of impact loading (IL) suggest that IL prior to menarche is associated with postmenarche diaphysis size and strength increases in women (Murray and Erlandson 2021). Longitudinal study of pre-menarchal gymnasts, who left the sport before menarche, found that the gymnasts sustained higher forearm BMC, forearm areal bone mineral density (aBMD), and area for at least two years after menarche, compared to controls (Scerpella et al 2010).…”
Section: Msms and Entheseal Changesmentioning
confidence: 99%